Telehealth use in the well-child health setting. A systematic review of acceptability and effectiveness for families and practitioners - Kim Howland; Kristina Edvardsson; Helen Lees; Leesa Hooker (International Journal of Nursing Studies Advances)
Background: Universal well-child health nursing services in high-resource countries promote the health and well-being of children and families while preventing health inequities. The COVID-19 pandemic and technological advancements have led to the increased use of telehealth in this field. To enhance policies and practices, it's important to understand the acceptability and effectiveness of telehealth, as well as the barriers and enablers to its implementation, and to determine when its use is appropriate and safe. Objective: To explore the global evidence on the use of telehealth in well-child health settings within high-income countries. Focussing on the effectiveness and acceptability of telehealth, along with the factors affecting its implementation and the considerations for safety from the perspectives of both providers and families. Design: A mixed methods systematic review Methods: A systematic review was conducted following PRISMA guidelines. The inclusion criteria for the review included: primary research papers written in English, conducted in high-income countries, focused on telehealth in the well-child health setting, and involving children under six years of age. The search, which was completed in July 2023, systematically explored the CINAHL, ProQuest Central, PubMed, and Web of Science bibliographic databases. Studies were critically appraised for quality, and relevant data extracted. A convergent segregated approach was employed to synthesise both quantitative and qualitative data, which is presented in a narrative format. Results: A total of 4,354 records were identified and screened, and 169 full-text papers were assessed for eligibility, resulting in 20 papers for inclusion. Telehealth acceptability among families was reported in 13 of the 20 studies reviewed, with participants expressing high satisfaction regarding its use as a complement to standard care. Only three studies examined practitioners' acceptance, revealing mixed responses. Effectiveness was observed in 15 studies, with no significant differences found between the control and telehealth groups, suggesting that telehealth may achieve outcomes like those of standard care. Four studies identified both enablers and barriers to the implementation of telehealth, though none addressed concerns regarding safety and appropriateness. Conclusions: Telehealth shows promise for well-child health services, but there is limited evidence of its effectiveness and safety. The COVID-19 pandemic increased its use, yet risks need further exploration. To validate telehealth in this field, we must identify effective applications, tackle implementation barriers, and ensure client safety. Additional research is essential for developing evidence-based policies for future practices.